The need for speed - Jean-Claude Kieffer (Canadian Science Publishing, 2021)
This paper reviews the challenges posed by the physics of the interaction of high-peak power femtosecond lasers with ultrathin foil targets. Initially designed to produce warm solid-density plasmas through the isochoric heating of solid matter, the interaction of an ultrashort pulse with ultrathin foils is becoming more and more complex as the laser intensity is increased. The dream of achieving very hot solid density matter with extreme specific energy density faces several bottlenecks discussed here as related to the laser technology, to the complexity of the physical processes, and to the limits of our current time-resolved instrumentations.